PERAN KEPUASAN DAN KEPERCAYAAN DALAM MEMEDIASI PENGARUH BAURAN PEMASARAN TERHADAP LOYALITAS KONSUMEN PADA PT BINTANG MAS INDONESIA - Ediyanto Ediyanto (Relawan Jurnal Indonesia, 2016)
The purpose of this research was to analyze the impact of marketing mix to customer loyalty with satisfaction and trust as mediating variable at Bintang Mas Indonesia. Data were gathered by distributing questionnaire to 112 respondents with purposive sampling. To analysis the data, this research used Strusctural Equation Modelling (SEM). The result of this analysis showed that marketing mix had positive significant effect to satisfaction, marketing mix had positive significant effect to loyalty, satisfaction had positive significant effect to trust, satisfaction had positive significant effect to loyalty, and trust had not positive significant effect to loyalty.